2019
DOI: 10.1039/c9fo00480g
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of dietary gardenia blue pigment derived from genipin and tyrosine

Abstract: Gardenia blue pigments derived from genipin reacting with amino acids have antidepressant effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Additionally, the activity of the HPA axis is also regulated by proinflammatory cytokines, such as IL-6, IL-1β, and TNF-α, which can easily cross BBB and exert their effects through various cytokine receptors [9]. In Li's study, elevated CORT levels were observed in the plasma and hippocampus after the administration of LPS [189]. It has also been indicated that an intraperitoneal injection of IL-1 administered to rats activated the HPA axis by increasing the ACTH and corticosterone levels in plasma [190].…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 97%
“…Additionally, the activity of the HPA axis is also regulated by proinflammatory cytokines, such as IL-6, IL-1β, and TNF-α, which can easily cross BBB and exert their effects through various cytokine receptors [9]. In Li's study, elevated CORT levels were observed in the plasma and hippocampus after the administration of LPS [189]. It has also been indicated that an intraperitoneal injection of IL-1 administered to rats activated the HPA axis by increasing the ACTH and corticosterone levels in plasma [190].…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 97%
“…Further, crocin significantly increases the expression of p-CREB, brain-derived neurotrophic factor (BDNF), and vascular endothelial growth factor (VEGF) in the rat hippocampus [ 13 ]. Our previous research showed that Yueju pills [ 14 ] and gardenia [ 15 ] have antidepressant effects, with gardenia yellow pigment (GYP, a collection of compounds with shared structure of crocin) being one of the constituents responsible for their antidepressant efficacy [ 16 ]. Transcriptomic analyses detected a unique upregulation of hippocampal PACAP expression post Yueju (unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are reported in a previous publication that cytokine responses to LPS are age- and tissue-dependent in neuroendocrine tissues of neonatal pigs ( 33 ). Some previous studies on mice or rats have shown that ACTH attenuated LPS-induced systematic inflammatory response ( 34 , 35 ). For example, it was reported that treatment with ACTH ( 1 24 ) sympathectomy attenuated LPS-induced increases of IL-1β, IL-6, and IL-10 levels in the plasma of rats.…”
Section: Discussionmentioning
confidence: 97%